FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS SIMPANG BAHJAMBI KABUPATEN SIMALUNGUN - Jon Piter Sinaga; Novi Silvia Vera (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
The increasing prevalence of hypertension each year is a major problem in developing and developed countries. This research was conducted at the post of integrated service of elderly Working area public health center of Simpang Bahjambi, Simalungun Regency. The type of research is a descriptive correlation and using stratified random sampling technique the total sample is 88 respondents. Data were analyzed by using the chi-square test and multiple linear regression tests at 95% confidence. The results of this research show that there is no relationship between the habit of consuming alcoholic beverages with the incidence of hypertension. There was a significant relationship between age, gender, and family disease history. BMI, smoking, and stress with the incidence of hypertension in the elderly. From multiple linear regression tests, found that the most dominant variable correlated significantly with the incidence of hypertension for the elderly is the age factor. It is expected that the society to find information about hypertension disease for the elderly who expected the information is useful and can influence the change of elderly attitude in order to make efforts to control hypertension, besides that the elderly family also willing to make efforts of supervision on family members who suffer from hypertension.